ANALISIS KESTABILAN MODEL LERENG TANAH PASIR KELEMPUNGAN TERHADAP GETARAN DI LABORATORIUM - Haryanto, Andre Yongsin; Tjandra, Daniel; Wulandari, Paravita Sri (Program Studi Magister Teknik Sipil - Petra Christian University, 2026)
Steep slope conditions combined with the influence of vibrations can lead to landslides. Therefore, slope stability is crucial in highland areas. This study aims to analyze the effect of vibrations on the stability of sandy clay slopes with varying sand and clay compositions of 70%:30%, 60%:40%, and 50%:50%, as well as slope angles of 45° and 60°. The research began with soil characterization tests and a Proctor test. Subsequently, vibration simulations were conducted using a vibrator machine. The results showed that variations in clay content and slope angle influence the landslide patterns that occur when the slope is subjected to vibrations. The higher the sand content, the greater the potential for landslides due to decreased soil stability under vibration. Additionally, the steeper the slope, the higher the risk of landslides.